2012
DOI: 10.1007/s11251-012-9231-8
|View full text |Cite
|
Sign up to set email alerts
|

From the lab to the dorm room: metacognitive awareness and use of spaced study

Abstract: Numerous laboratory studies have demonstrated the long-term memory benefits of studying material in multiple distributed sessions as opposed to one massed session, given an identical amount of overall study time (i.e., the spacing effect). The current study goes beyond the laboratory to investigate whether undergraduates know about the advantage of spaced study, to what extent they use it in their own studying, and what factors influence its utilization.Participants (n = 285) completed a web-based survey respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
76
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 27 publications
6
76
1
3
Order By: Relevance
“…Despite the fairly robust benefits of retrieval—even in course environments using material from the curriculum (e.g., McDaniel et al , 2007, 2013; Carpenter et al , 2009, 2016; Roediger et al , 2011)—survey research on students’ self-reported study habits has revealed that students seldom use retrieval as a study tool (Karpicke et al , 2009; Susser and McCabe, 2013). Other survey research has shown that, when students do use retrieval-based study techniques (e.g., flash cards, practice questions), the majority of students report doing so in order to check their understanding rather than to directly improve their learning (Kornell and Bjork, 2007; Hartwig and Dunlosky, 2012; Yan et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fairly robust benefits of retrieval—even in course environments using material from the curriculum (e.g., McDaniel et al , 2007, 2013; Carpenter et al , 2009, 2016; Roediger et al , 2011)—survey research on students’ self-reported study habits has revealed that students seldom use retrieval as a study tool (Karpicke et al , 2009; Susser and McCabe, 2013). Other survey research has shown that, when students do use retrieval-based study techniques (e.g., flash cards, practice questions), the majority of students report doing so in order to check their understanding rather than to directly improve their learning (Kornell and Bjork, 2007; Hartwig and Dunlosky, 2012; Yan et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Survey research on students' approaches to studying reveals that, contrary to the widespread benefits of retrieval and distributed practice, students often report re-reading course material and cramming shortly before the test (Hartlep & Forsyth, 2000;Susser and McCabe, 2013). For example, McCabe (2011) presented students with six hypothetical learning scenarios that involved choosing one of two study strategies, either an optimal strategy (e.g., testing) or a sub-optimal strategy (e.g., restudying), and found that students rarely (23%) endorsed the optimal strategy.…”
Section: Achievement Goalsmentioning
confidence: 99%
“…They noted that this could merely be due to divergence between what people think is a random distribution and what is actually random, but it could also reflect a real appreciation that spacing restudy opportunities is beneficial. Additionally, Susser and McCabe (2013) found that college students report being more likely to space study sessions across multiple days in real-world learning situations when an upcoming exam is more difficult or more important, or when they have fewer competing academic priorities. Thus, there is some reason to believe that the choice of later restudy in previous laboratory studies does reflect an appreciation for the benefits of spaced practice, but the question remains to be fully resolved.…”
Section: Metacognitive Control Of Spacingmentioning
confidence: 99%